Breaking the Chains of Stigma: Psychodrama and Kuda Lumping Unite to Empower Cancer Patients in Society - Ananingsih, Esti Sri; Afrilia, Dian; Suryaningtyas, Winda; Khodijah, Salma (International Journal Scientific and Professional, 2025)
Cancer, a formidable and life-altering disease, often carries with it a heavy burden of stigma that devastates not only the physical well-being of patients but also their emotional and social lives. The deep-rooted fear and misconceptions about cancer lead to alienation, isolation, and an exacerbation of the patient’s suffering. This study embarks on an audacious journey to challenge this stigma by merging the therapeutic power of psychodrama with the rich cultural heritage of Kuda Lumping, a Javanese traditional performance symbolizing strength, resilience, and unity. Using a bold, participatory action research approach, this intervention weaves together the art of psychodrama with cultural rituals, inviting cancer patients, their families, and the broader community to engage in a profound collective experience. The result? A revolutionary shift in perception. Through powerful role-playing and symbolic acts, participants broke down barriers of fear, ignorance, and judgment. The Kuda Lumping dance became more than just a performance—it became a transformative ritual that empowered both patients and community members to confront and dismantle the stigma surrounding cancer. By the end of the intervention, 80% of participants reported a profound shift in their understanding of cancer, with 70% expressing newfound empathy and commitment to supporting those affected by the disease. This study underscores the transformative power of combining psychological therapy with cultural heritage, offering a powerful blueprint for future health interventions. It stands as a testament to the potential of psychodrama, enriched with local cultural elements, to heal and unite communities, and to finally break the chains of cancer stigma that have long bound society in silence and fear.